A Switchable Domino Process for the Construction of Novel CO2‐Sourced Sulfur‐Containing Building Blocks and Polymers. Issue 34 (18th July 2019) - Ouhib, Farid; Grignard, Bruno; Van Den Broeck, Elias; Luxen, André; Robeyns, Koen; Van Speybroeck, Veronique; Jerome, Christine; Detrembleur, Christophe
Abstract: α‐Alkylidene cyclic carbonates (αCCs) recently emerged as attractive CO2 ‐sourced synthons for the construction of complex organic molecules. Herein, we report the transformation of αCCs into novel families of sulfur‐containing compounds by organocatalyzed chemoselective addition of thiols, following a domino process that is switched on/off depending on the desired product. The process is extremely fast and versatile in substrate scope, provides selectively linear thiocarbonates or elusive tetrasubstituted ethylene carbonates with high yields following a 100 % atom economy reaction, and valorizes CO2 as a renewable feedstock. It is also exploited to produce a large diversity of unprecedented functional polymers. It constitutes a robust platform for the design of new sulfur‐containing organic synthons and important families of polymers. Abstract : High atom economy : Linear thiocarbonates and elusive tetrasubstituted ethylene carbonates are accessible in high yields from the organocatalyzed chemoselective addition of thiols to α‐alkylidene cyclic carbonates thanks to a switchable domino process. This robust synthetic method is also exploited for the facile construction of a large diversity of unprecedented sulfur‐containing polymers.